Cobalt selenide nanorods used as a high efficient counter electrode for dye-sensitized solar cells. (20th June 2015) - Dong, Jia; Wu, Jihuai; Jia, Jinbiao; Wu, Shaoyun; Zhou, Pei; Tu, Yongguang; Lan, Zhang
Abstract: Cobalt selenide (CoSe2 ) nanorods are prepared by hydrothermal method and used as an efficient Pt-free counter electrode (CE) for dye-sensitized solar cells (DSSCs). Field emission scanning electron microscopy observes that CoSe2 mostly exhibits a nanorod morphology, which facilitates change carrier transfer from their surface to redox electrolyte. Cyclic voltammogram measurement indicates that CoSe2 electrode has larger current density than Pt electrode. Electrochemical impedance spectroscopy shows that the CoSe2 electrode with optimal condition has low series resistance of 8.034 Ω × cm 2 and has low charge-transfer resistance of 0.097 Ω·cm 2 . Under simulated solar light irradiation with intensity of 100 mW·cm −2 (AM 1.5), the DSSC based on the CoSe2 CE achieves a power conversion efficiency of 8.38 %, which is higher than the solar cell based on Pt CE (7.83%).